Constructing Synergistic Zn‐N4 and Fe‐N4O Dual‐Sites from the COF@MOF Derived Hollow Carbon for Oxygen Reduction Reaction. Issue 4 (23rd February 2022) - Miao, Qiyang; Yang, Shuai; Xu, Qing; Liu, Minghao; Wu, Ping; Liu, Guojuan; Yu, Chengbin; Jiang, Zheng; Sun, Yuhan; Zeng, Gaofeng
Abstract : Dual‐metal atom catalysts have been demonstrated to display higher catalytic activity and selectivity than that of solo metal atom catalysts toward oxygen reduction reaction (ORR). However, it is difficult to construct synergistic sites between different atoms even though they are immobilized in the same support, because their low‐density distribution resulted in the long distance between each other. Herein, a synergistic bimetal atomic electrocatalyst for ORR, which has highly dense Zn‐N4 (12.2 wt.% for Zn) and Fe‐N4 O sites, from a core–shell hybrid of a covalent organic framework (COF) and a metal–organic framework (MOF) is demonstrated. The resultant catalyst displays a high activity for ORR with a half‐wave potential of 0.89 V vs reversible hydrogen electrode (RHE) in 0.1 m KOH, which is 50 mV more positive than that of Pt/C. The operando ANES confirms both Zn and Fe sites in the catalyst as active centers, and demonstrates that Fe sites have higher activity in the ORR process. Density functional theory (DFT) calculations further confirm the synergistic effect enables to improve the activity for both Fe sites and Zn sites in ORR. This work provides a new insight to develop ORR catalysts from COFs and MOFs. Abstract : A high‐density Zn‐N4 atoms doped hollow carbon from the hybrid of COF and MOF is fabricated. With chelating FePc on the surface through oxygen atoms, the catalyst has FeN4 O and ZnN4 dual‐sites. The synergistic effect between the Fe and Zn sites makes the catalysts catalyze oxygen reduction reaction (ORR) with high activity and selectivity.